Cognitive foundations of entrepreneurship: creativity and opportunity recognition - Baron, Robert A. (Henry Stewart Talks, 2011)
Basic nature of cognition, Limits of human cognition, How information is stored in memory, A cognitive perspective answers basic questions concerning entrepeneurship, Cognitive biases, Creativity, The role of concepts in creativity, Opportunity recognition, Role of pattern recognition in opportunity recognition